2021
DOI: 10.1016/j.cegh.2021.100788
|View full text |Cite
|
Sign up to set email alerts
|

Biological attributes of age and gender variations in Indian COVID-19 cases: A retrospective data analysis

Abstract: Background: The associated risk factors, co-morbid conditions and biological differences varying with gender and age might be the cause of higher COVID-19 infection and deaths among males and older persons. The objective of this study was to predict and specify the biological attributes of variation in age and gender-based on COVID-19 status (deceased/recovered). Methods: In this retrospective study, the data was extracted from a recognised web-based portal. A total of 112,860 patients' record was filtered out… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
32
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 28 publications
8
32
2
2
Order By: Relevance
“…Overall COVID-19 numbers were higher in males, however the numbers were similar for those who were between 31 and 60 years. This was different to other findings which indicated that females below age 35 years had higher chances of getting infected than males in the same age category ( 20 ). Over the review period, the prevalence rates for positive COVID-19 tests at admission for males and females were 7.2%(639/8837) and 3.6%(322/8837) respectively.…”
Section: Discussioncontrasting
confidence: 99%
“…Overall COVID-19 numbers were higher in males, however the numbers were similar for those who were between 31 and 60 years. This was different to other findings which indicated that females below age 35 years had higher chances of getting infected than males in the same age category ( 20 ). Over the review period, the prevalence rates for positive COVID-19 tests at admission for males and females were 7.2%(639/8837) and 3.6%(322/8837) respectively.…”
Section: Discussioncontrasting
confidence: 99%
“…Among the COVID-19-positive patients, male was predominant. This was consistent with other nearby countries such as India, where researcher reported that male COVID-19 cases (65.39%) were more than females (34.61%) 23. This might be due to the male-dominant societies’ unique health-seeking behaviour like Bangladesh, where women do not seek healthcare unless severe 24.…”
Section: Discussionsupporting
confidence: 87%
“…This was consistent with other nearby countries such as India, where researcher reported that male COVID-19 cases (65.39%) were more than females (34.61%). 23 This might be due to the maledominant societies' unique health-seeking behaviour like Bangladesh, where women do not seek healthcare unless severe. 24 This finding was similar (68% male) during March-April, the early phase of novel coronavirus detection in Bangladesh.…”
Section: Openmentioning
confidence: 99%
“…The major reasons for the poor performances of these states, specifically in terms of health outcomes and high mortality rates, include poverty, overpopulation, low literacy levels, gender discrimination, and poor health infrastructure [12]. Though biological differences exist between the genders however [13]; the health outcome differences and inequalities are more evident in the case of rural Indian women. Women face diverse socio-economic and cultural issues attributed in terms of gender discrimination, such as female infanticide, child marriage, dowry, domestic violence, lack of education, and unavailability of proper sanitation and healthcare facilities [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Though biological differences exist between the genders however [13]; the health outcome differences and inequalities are more evident in the case of rural Indian women. Women face diverse socio-economic and cultural issues attributed in terms of gender discrimination, such as female infanticide, child marriage, dowry, domestic violence, lack of education, and unavailability of proper sanitation and healthcare facilities [14–16].…”
Section: Introductionmentioning
confidence: 99%